2009
DOI: 10.1007/s12325-009-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 inhibitors: from sitagliptin monotherapy to the new alogliptin-pioglitazone combination therapy

Abstract: Diabetes mellitus (DM) is currently considered to be an epidemic disease. A safe and effective treatment has long been sought by scientists. Incretin mimetics and dipeptidyl peptidase-4 (DPP4) inhibitors represent a new class of agents that have recently been included as antidiabetic drugs. Although only a limited number of studies exist regarding the treatment of DM based on the incretin effect, DPP4 inhibitors have so far proved to be safe and effective, both when administered alone or in combination with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Sitagliptin as a novel T2DM therapy improves alpha islet function due to the increased concentrations of active GLP-1, which stimulates insulin secretion and inhibits glucagon secretion. 47 In one study, 48 sitagliptin (100 mg) reduced HbA 1c by 0.6% from a baseline of 7.7% in 555 subjects. Another study, 49 comprising 743 subjects, reported that sitagliptin reduced HbA 1c by 0.8% from a baseline of 7.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Sitagliptin as a novel T2DM therapy improves alpha islet function due to the increased concentrations of active GLP-1, which stimulates insulin secretion and inhibits glucagon secretion. 47 In one study, 48 sitagliptin (100 mg) reduced HbA 1c by 0.6% from a baseline of 7.7% in 555 subjects. Another study, 49 comprising 743 subjects, reported that sitagliptin reduced HbA 1c by 0.8% from a baseline of 7.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, greater reductions in HbA1c levels were identified when alogliptin was combined with pioglitazone, without elevating the possibility of hypoglycaemic events ( Deacon, 2011 ). The therapeutic effectiveness of alogliptin-pioglitazone combination deserves attention in the future management of T2DM ( Argyrakopoulou and Doupis, 2009 ).…”
Section: Dpp-4 Inhibitors: Current Statusmentioning
confidence: 99%
“…Independently, sitagliptin inhibits the degradation of incretins, GLP-1, and glucose-dependent insulinotropic peptide by inhibiting DPP-4 (a GLP-1-inactivating peptide), which serve to initiate the secretion of postprandial insulin [ 32 , 37 ]. Considering a few clinical trials that investigated the efficacy of sitagliptin, it can be used as a relatively safe antidiabetic treatment that works independently but shows greater effectiveness when administered as an adjunct therapy with BC [ 38 ]. In a 2018 experimental study, induced diabetic rats were treated with BC, sitagliptin 10 mg/kg orally (SG10), sitagliptin 20 mg/kg orally (SG20), and a combination of SG10+BC over two weeks.…”
Section: Reviewmentioning
confidence: 99%
“…For T2DM patients, the PPAR-γ pathway role is diminished, leading to insulin insensitivity [ 39 , 40 ]. Additionally, T2DM patients have a high activity of the Janus kinase (JAK)/signal transducer and activator of transcription proteins (STAT) pathway, which induces the inflammation of endothelial cells via interleukin-6 [ 38 ]. The BC+SG10 treatment results indicated that both pathways were involved.…”
Section: Reviewmentioning
confidence: 99%